2020
DOI: 10.2147/dhps.s266749
|View full text |Cite
|
Sign up to set email alerts
|

<p>Assessment of Drug Use Pattern Using WHO Core Prescribing Indicators at Outpatient Settings of Governmental Hospitals in Dessie Town</p>

Abstract: Background: Enhancing the standards of medical treatment at all levels of the healthcare delivery system can improve the quality of life in developing countries. One method to promote rational drug use is an assessment of drug use pattern based on drug use indicators. Objective: To evaluate prescription patterns at the outpatient pharmacy of Dessie Referral Hospital and Boru Meda Hospital at Dessie town. Methods: An institution-based retrospective cross-sectional study was conducted to assess the prescribing p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
8
6

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(25 citation statements)
references
References 25 publications
(96 reference statements)
7
8
6
Order By: Relevance
“…In order to identify patients during the dispensing process, prescribers should be aware of the signi cance of writing the patient's name on each and every prescription paper. The percentage of prescription papers with age written in the current study was 92.55%, which is consistent with a study conducted in Bahir Dar and Dessie, Ethiopia, where 92.6% and 93.5% were reported 40,43 .…”
Section: Prescribing Pattern Indicatorssupporting
confidence: 91%
See 4 more Smart Citations
“…In order to identify patients during the dispensing process, prescribers should be aware of the signi cance of writing the patient's name on each and every prescription paper. The percentage of prescription papers with age written in the current study was 92.55%, which is consistent with a study conducted in Bahir Dar and Dessie, Ethiopia, where 92.6% and 93.5% were reported 40,43 .…”
Section: Prescribing Pattern Indicatorssupporting
confidence: 91%
“…The result, however, is lower than that of the study conducted in Harar (32.7%) and higher than those from Bahir Dar (8.3%) and Jimma (11.45%) in Ethiopia 41,45,46 . The method of drug administration was noted on 84.62% of prescription papers in the current study, which is roughly equivalent to earlier ndings from Harar, 81.8% 45 and Dessie, 82.2% 43 in Ethiopia. but less than previous studies of a comparable studies that reported between 88.1 and 93.1% 42,44,46 .…”
Section: Prescribing Pattern Indicatorssupporting
confidence: 89%
See 3 more Smart Citations